MEASURING USABILITY TESTING BY THE ONLINE APPLICATION START EBNP QUESTIONNAIRE - Anggit Prasetyo Mituhu; Tri Nur Kristina; Luky Dwiantoro (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Evidence-Based Nurse Practice (EBNP) is used to enhance the quality of nursing by considering internal evidence, external evidence, and patient assessment. In reality, applying EBNP has many problems such as knowledge level, lack of time, facilities, and management support such as training and seminar. The development of technology gives chances for the massive promotion of EBNP. Objective: This application is newly made and its pilot study aims at finding the answer to the usability and accessibility of online application START EBP. Design: This study used a cross-sectional study method. The target population in this study was 112 clinical nurses. The sampling technique used was purposive sampling. The sample size in the pilot study was 12 respondents. This research is a kind of research and development study. The new application is Online START EBP that uses seven levels of applying EBP. The data analysis carried out was usability test. Results: The results of 12 respondents selected from 112 populations by purposive sampling shows that the users are easier to learn and memorize the interface of the application START EBP in total averaged scored 3.24 point. The reliability results show an alpha value of 0.920, so the reliability is in the perfect category. Conclusion: The START EBP online application is easy to use because it is easy to understand by users.